An Application of the Multi-Level Heuristic for the Heterogeneous Fleet Vehicle Routing Problem - Imran, Arif (JURNAL ITENAS REKAYASA, 2010)
ABSTRACTThe Multi-Level heuristic is used to investigate the heterogeneous fleet vehicle routing problem (HFVRP). The initial solution for the Multi-Level heuristic is obtained by Dijkstra’s algorithm based on a cost network constructed by the sweep algorithm and the 2-opt procedure. The proposed algorithm uses a number of local search operators such as swap, 1-0 insertion, 2-opt, and Dijkstra’s Algorithm. In addition, in order to improve the search process, a diversification procedure is applied. The proposed algorithm is thentested on the data sets from the literature.Keywords: multi-level, heuristic, routing, heterogeneous fleet  ABSTRAKAlgoritma Multi-Level heuristic digunakan untuk melakukan investigasi terhadap heterogeneous fleet vehicle routing problem (HFVRP). Solusi inisial Multi-Level heuristic didapatkan dari algoritma Dijkstra berdasarkan cost network yang dibentukoleh agoritma sweep dan prosedur 2-opt. Algoritma Multi-Level heuristic yang dikembangkan memakai sejumlah operator local search seperti, swap, 1-0 insertion, 2-opt, and algoritma Dijkstra. Untuk memperbaiki proses pencarian solusi (search process) satu prosedur diversifikasi juga diaplikasikan. Selanjutnya, algoritma yang dikembangkan diuji untuk menyelesaikan data-data yang terdapat pada literatur.Kata kunci: multi-level, heuristik, ruting, heterogeneous fleet